2013
DOI: 10.1016/j.neuron.2013.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Beclin 1 Regulates Retromer Trafficking and Phagocytosis and Is Impaired in Alzheimer’s Disease

Abstract: SUMMARY Phagocytosis controls CNS homeostasis by facilitating the removal of unwanted cellular debris. Accordingly, impairments in different receptors or proteins involved in phagocytosis result in enhanced inflammation and neurodegeneration. While various studies have identified extrinsic factors that modulate phagocytosis in health and disease, key intracellular regulators are less understood. Here we show that the autophagy protein beclin 1 is required for efficient phagocytosis in vitro and in mouse brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
285
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(311 citation statements)
references
References 60 publications
16
285
1
3
Order By: Relevance
“…1B). Given TREM2 is predominantly expressed in microglia in the brain (27), we sought to further confirm our findings in the immortalized murine microglial cell line BV2, a model frequently used for in vitro studies of microglial functions (28,29). Consistent with our findings in HEK293T cells, the level of TREM2-CTF was significantly elevated in the presence of DAP12 co-expression in BV2 cells (Fig.…”
Section: Resultssupporting
confidence: 78%
“…1B). Given TREM2 is predominantly expressed in microglia in the brain (27), we sought to further confirm our findings in the immortalized murine microglial cell line BV2, a model frequently used for in vitro studies of microglial functions (28,29). Consistent with our findings in HEK293T cells, the level of TREM2-CTF was significantly elevated in the presence of DAP12 co-expression in BV2 cells (Fig.…”
Section: Resultssupporting
confidence: 78%
“…In a recent study in mice, Safaiyan et al (2016) identified an age-related increase in Gal-3 microglia and an increase in microglia contacting myelin visualized by double-label IHC, suggesting that microglia not only have increased phagocytic activation but also that this increased activation may be related to myelin. Similar inefficient debris clearance has been seen in age-related neurodegenerative diseases such as Alzheimer's, where β-amyloid aggregation is also thought to be related to an impaired phagocytic capacity of microglia (Chung et al 1999;Lucin et al 2013;Hickman and El Khoury 2014). These data suggest that age-related impairment of microglial phagocytosis is not limited to myelin.…”
Section: Phagocytic Capacity and Age-related Neurodegenerative Diseasessupporting
confidence: 59%
“…Somehow unexpectedly, retromer has been recently linked to another pathological feature of AD, namely microglia abnormalities [21]. Glia abnormalities were actually first described by Alois Alzheimer, and together with amyloid plaques and neurofibrillary tangles, is a third histological feature of the disease that bears his name.…”
Section: Small Molecules As Retromer Chaperonesmentioning
confidence: 98%
“…Glia abnormalities were actually first described by Alois Alzheimer, and together with amyloid plaques and neurofibrillary tangles, is a third histological feature of the disease that bears his name. A recent study found that Vps35 is deficient in microglia harvested from AD brains and that retromer in microglia is required for the normal cell surface delivery of 2 microglia-enriched receptors-Trem2 and CD36 [21]. AD-linked variants have been found in the gene encoding Trem2 [22], and the normal cell surface delivery of CD36 is required for the microgliameditated Aβ-clearing effects.…”
Section: Small Molecules As Retromer Chaperonesmentioning
confidence: 99%